1994
DOI: 10.1002/jctb.280610103
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization of bituminous and lignite coals by chemically and biologically synthesized surfactants

Abstract: Tween 80 (polyoxyethylene sorbitan monooleate), Triton X‐100 (nonaethylene glycol octylphenol ether), and SDS (sodium dodecyl sulfate) solubilized several components of Mississippi Wilcox lignite and Illinois No. 6 bituminous coal. Tween 80 extraction of alkali‐soluble Ugljevik lignite resulted in an increase in hydrogen content and decreases in the nitrogen and sulfur contents of undissolved coal solids. Biosurfactant‐containing cell‐free extracts of Bacillus licheniformis solubilized a 53 000 Da coal compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 18 publications
0
6
0
2
Order By: Relevance
“…O biodispersan, polissacarídeo aniônico, produzido por A. calcoaceticus A2, foi utilizado na prevenção da floculação e dispersão de misturas de pedra calcárea e água 42 . Biossurfactantes de C. bombicola demonstraram eficiência na solubilização de carvão 43 .…”
Section: Biossurfactantes Na Mineraçãounclassified
“…O biodispersan, polissacarídeo aniônico, produzido por A. calcoaceticus A2, foi utilizado na prevenção da floculação e dispersão de misturas de pedra calcárea e água 42 . Biossurfactantes de C. bombicola demonstraram eficiência na solubilização de carvão 43 .…”
Section: Biossurfactantes Na Mineraçãounclassified
“…POLMAN and coworkers used three chemosurfactants (Tween 80, Triton-X-100, SDS) and two biological surfactants (from the bacterium Bacillus licheniformis and the yeast Candida bombicola) to "dissolve" different coals or coal fractions (POLMAN et al, 1994a;BRECKENRIDGE and POLMAN, 1994). POLMAN and coworkers used three chemosurfactants (Tween 80, Triton-X-100, SDS) and two biological surfactants (from the bacterium Bacillus licheniformis and the yeast Candida bombicola) to "dissolve" different coals or coal fractions (POLMAN et al, 1994a;BRECKENRIDGE and POLMAN, 1994).…”
Section: Non-enzymatic Effectorsmentioning
confidence: 99%
“…15 Furthermore, it has been shown that lignite components can be solubilized using biosurfactant-containing cell-free ltrate (CFF) extracted from Bacillus licheniformis. 21 Most coal-solubilizing bacteria and actinomycetes primarily rely on alkaline action and chelation, while fungi mostly rely on enzymes, but also utilize the above substances to a lesser degree. 22,23 Although extracellular metabolites are widely known for their role in the lignite solubilization process, research on process optimization of HA extraction from lignite using extracellular CFF is still scarce.…”
Section: Introductionmentioning
confidence: 99%